Boron neutron capture therapy for melanoma: recent advances and future prospects - Sun, Yuanyang; Wang, Yun; Mu, Shukun; Wu, Xiaofeng; Yu, Suchun; Wang, Zhongming (Frontiers in Oncology, 2025)
Boron neutron capture therapy (BNCT) is a unique radiotherapy modality that targets and destroys selectively tumor cells that have absorbed boron, while leaving surrounding healthy cells unharmed. Over the course of the last nearly 40 years, several clinical studies of BNCT for melanoma have been conducted in many countries. The results of clinical studies are encouraging, suggesting that BNCT may be a potentially effective method for treating melanoma. In this work, we review the outcomes of clinical study of BNCT for melanoma. Moreover, we provide a concise overview of advancements in accelerator-based neutron source and boron delivery agent (BDA) applied to BNCT for melanoma. Finally, we discuss the areas for further research focus regarding BNCT for melanoma.